Compact plant type rice has higher lodging and N resistance under machine transplanting - Chao DING; Xi-kun LUO; Qiong WU; Bo LU; Yan-feng DING; Jiuzhou SONG; Gang-hua LI (Journal of Integrative Agriculture, 2021)
To identify the major factors that contribute to the difference in lodging among different rice varieties under machine transplanting and their responses to nitrogen (N), field experiments were conducted at Danyang County (a representative eco-site of the Lower Yangtze River) in Jiangsu Province, China in 2017 and 2018, 22 hybrid indica varieties (HIs), 22 inbred japonica varieties (IJs) and two indica japonica hybrid varieties (IJHs) were transplanted by machine with three N rates (N0, N150 and N300, 0, 150 and 300 kg ha–1, respectively). Lodging-related physical parameters, morphological characteristics and apparent transport rates of dry matter were examined. Significant difference in yield was observed among different types of rice, and followed by IJs<HIs<IJHs. The average lodging index (LI) of hybrid varieties (HIs and IJHs) was higher than that of the inbred varieties (IJs) with higher plant height; moreover, lower apparent export rate of dry matter resulted lower LI in IJHs than in HIs. The HIs had a large difference in the LI, which came from the difference in bending stress (BS) induced by the difference in the apparent export rate of dry matter, varieties with lower leaf angle of upper three leaves possess strong lodging resistance capacity; however, the gap among the IJs was due to the difference in the cross section modulus (Z). The LI in the IJs or IJHs increased slightly with the increased N application, and there was no lodging incidence under the high N level, which was due to the low leaf angle and barely changed under high N; there was a significant interaction between varieties (HIs) and N rates in lodging rate and LI, varieties with lower leaf angle of upper three leaves were resistant to high N. These results suggest that compact plant type rice has higher lodging and N resistance at machine-transplanting method.